SOCIAL INTERACTION THROUGH @RABBITHOLEID IN TRANSFER OF INFORMATION - Anjelin Rahmi Junaidi Harahap; Franindya Purwaningtyas (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
The various information needs of users usually trigger a high curiosity about a particular topic. The existence of different information needs is what makes users transfer information to each other through social interaction. It is possible that this process occurs on a social media platform such as the rabbitholeid Instagram account. Information transfer and social interaction are related to each other because social interaction can be an important channel for the transfer of information between individuals or groups. The social interaction that causes the media transfer process is what occurs in the discussion in the comments column on the rabbitholeid account. The purpose of this research is to find out how the process of transferring information from the results of social interaction on the rabbitholeid Instagram account occurs. Through this study, it is hoped that later we will be able to find out how the process of transferring information that occurs on the account is made, especially with the social interactions that are carried out. In addition, this study also has problem limitations where the author will review in detail the cause and effect and the process of transferring information through social interaction on rabbitholeid accounts only so that it does not expand to a wider scope.